Sustainable social mobility among Indigenous communities: a bibliometric analysis - Ramaprabha, N.; Balamurugan, J. (Frontiers in Human Dynamics, 2025)
IntroductionSocial mobility is among the debated topics by researchers and policymakers today. This paper offers a comprehensive literature review in relation to sustainable social mobility among Indigenous communities.MethodsThis study employed bibliometric analysis using the Scopus database and the Preferred Reporting Items for Systematic Reviews and Meta-Analysis, or PRISMA, flowchart. A total of 628 publications between 2001 and 2023 were analyzed using the keywords associated with social sustainability, mobility, and Indigenous communities.ResultsResearch output has increased significantly since 2011. The countries with such outputs are mostly the United Kingdom, Italy, and the United States. The most-cited article was titled “Sustainable development: Meaning, history, principles, pillars, and implications for human action: Literature review.”DiscussionThe research reveals emerging trends and gaps in the literature on sustainable social mobility. It mainly focuses on how environmental sustainability, digital technologies, and other methodologies help to understand social mobility. Of course, the study also showed interest in community projects and local knowledge that can support sustainable development and social mobility for Indigenous communities.